Pengaruh Reputasi Auditor dan Mekanisme Corporate Governance Terhadap Integritas Laporan (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2008-2010) - Fitri Damayanti; Rochmi Rochmi (Faculty of Economic and Business, 2014)
This study aims to obtain empirical evidence about the effect of auditor reputation, corporate governance mechanism (independent commissioner managerial ownership, institutional ownership) to integrity of financial statement at the manufacturer companies in Indonesia. Integrity of financial statement define as how far a financial statement disclosure shows truth and honest information. Independent variables used in this study were reputation auditor and corporate governance mechanism was analyzed by independent commissioner managerial ownership, institutional ownership. Dependent variable used in this study is integrity of financial statement was analyzed by conservatism. Study’s sample was manufacturer companies listed in Indonesia Stock Exchange (IDX) period among 2008-2010. Data was collected by purposive sampling method. Total 56 manufacturer companies were taken as study’s sample. The method of analysis of this research used multiple regression. The results of this research showed that reputation auditor and independent commissioner had significant effect to integrity of financial statement. Meanwhile, Institutional ownership and managerial ownership had not significant effect to integrity of financial statementDOI: 10.15408/ess.v4i3.2431